The identity of education professionals : positioning, training, and innovation - Monereo, Carles (Dialogical self theory., 2022)
"The 21st century and its many challenges (invasion of digital technology, climate change, health crises, political crises, etc.) alert us that we need new educational responses, led by new education professionals. Research has shown that for these professionals to change in a substantial and profound way, they must change their identity, that is, the way in which they give meaning and meaning to their professional work. This book exposes, based on one of the most current and advanced theories for analyzing identity change -the theory of the dialogic self-, what changes should take place and how to promote them in eleven fundamental professional profiles in current education (teachers of student-teachers, primary & secondary teachers, inclusive teachers, inquiring teachers, mentors, school principals, university teachers, academic advisors, technologic/hybrid teachers, Learning specialists & educational researchers)"--